Macro 향 캡슐의 제조 및 향 성분의 저장 안정성 - 차용준(Yong-Jun Cha); 김진현(Jin Hyeon Kim); 유대웅(Daeung Yu) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2021)
본 연구에서는 피복물질(wall material)로 알긴산과 Tween 60을 이용하였고 핵물질(core material)로는 혼합 허브향(레몬그라스:로즈마리:라벤더:시나몬, 3:3:3:1 비율, v/v)을 이용해 제조하여 macro 향 캡슐의 향 성분 안정성을 실험하였다. 향 캡슐의 저장 중 수분함량은 저장기간 동안 28일까지 점진적으로 감소하였다. 저장 중 향 보유율은 저장기간에 따라 감소해 10일경에 급격히 감소하였고(P<0.05) 그 후 33일경까지 감소한 다음 다시 증가하는 경향을 보인 반면, 향 캡슐의 sniffing 강도는 저장기간에 따라 감소하기만 하였다. 휘발성 향기성분을 분석한 결과 총 56종의 화합물이 동정되었는데, 이는 terpene류(18종), terpene alcohol류(17종), aldehyde와 ketone류(14종), ester류(6종) 및 acid(1종)로 구성되었다. 이 중 linalyl acetate의 함량이 10,039.48 μg으로 가장 많았으며, 그다음으로 linalool (4,375.41 μg), (E)-citral(4,246.77 μg), (Z)-citral(3,347.88 μg), eucalyptol(2,267.33 μg), camphor isomer(2,266.45 μg), (E)-cinnamaldehyde(1,880.33 μg) 순이었다. 혼합 향의 4가지 미생물에 대한 항균 효과는 향 함량이 1,000 ppm 이상인 20일경까지는 확실히 검증되었다. Macro fragrance capsule composed alginic acid, and Tween 60 as wall materials and mixed herbal scents (lemongrass, rosemary, lavender, and cinnamon, 3:3:3:1 ratio, v/v) as core material was prepared in this study, and the stability of the flavor compounds in macro fragrance capsule during storage was analyzed. The moisture content during the storage of the fragrance capsule gradually decreased to 28 day of storage. In the flavor holding capacity, the amount of flavor was volatilized with storage times, and the reduction up to 10 days was significant (P<0.05), and after that fluctuates, whereas the odor intensity of fragrance capsule decreased with storage times. A total of 56 compounds were identified, including terpenes (18), terpene alcohols (17), aldehydes and ketones (14), esters (6), and acid (1). The content of linalyl acetate was the most amount with 10,039.48 μg, followed by linalool (4,375.41 μg), (E)-citral (4,246.77 μg), (Z)-citral (3,347.88 μg), eucalyptol (2,267.33 μg), camphor isomer (2,266.45 μg), and (E)-cinnamaldehyde (1,880.33 μg) in that order. The antimicrobial activity of mixed fragrances against four of food poisoning bacteria was proved until 20 day, which is with over 1,000 ppm level. KCI Citation Count: 0